Does soil CuO nanoparticles pollution alter the gut microbiota and resistome of Enchytraeus crypticus?. (January 2020) - Ma, Jun; Chen, Qing-Lin; O'Connor, Patrick; Sheng, G. Daniel
Abstract: Growing evidence suggests that metallic oxide nanoparticles can pose a severe risk to the health of invertebrates. Previous attention has been mostly paid to the effects of metallic oxide nanoparticles on the survival, growth and physiology of animals. In comparison, the effects on gut microbiota and incidence of antibiotic resistance genes (ARGs) in soil fauna remain poorly understood. We conducted a microcosm study to explore the responses of the non-target soil invertebrate Enchytraeus crypticus gut microbiota and resistomes to copper oxide nanoparticles (CuO NPs) and copper nitrate by using bacterial 16S rRNA gene amplicons sequencing and high throughput quantitative PCR. The results showed that exposure to Cu 2+ resulted in higher bioaccumulation (P < 0.05) and lower body weight and reproduction (P < 0.05) of Enchytraeus crypticus than exposure to CuO NPs. Nevertheless, exposure to CuO NPs for 21 days markedly increased the alpha-diversity of the gut microbiota of Enchytraeus crypticus (P < 0.05) and shifted the gut microbial communities, with a significant decline in the relative abundance of the phylum Planctomycetes (from 37.26% to 19.80%, P < 0.05) and a significant elevation in the relative abundance of the phyla Bacteroidetes, Firmicutes and Acidobacteria (P < 0.05). The number of detected ARGs in the Enchytraeus crypticus gut significantly decreased from 45 in the Control treatment to 16 in the Cu(NO3 )2 treatment and 20 in the CuO NPs treatment. The abundance of ARGs in the Enchytraeus crypticus gut were also significantly decreased to 38.48% when exposure to Cu(NO3 )2 and 44.90% when exposure to CuO NPs (P < 0.05) compared with the controls. These results extend our understanding of the effects of metallic oxide nanoparticles on the gut microbiota and resistome of soil invertebrates. Graphical abstract: Image 1 Highlights: Exposure to Cu 2+ decreases the growth and reproduction of E. crypticus . CuO NPs alters the community composition of gut microbiota in E. crypticus . CuO NPs decreases the diversity and enrichment of ARGs in E. crypticu s gut. Abstract : Exposure to CuO nanoparticles perturbs the gut microbiota and decreases the resistome of Enchytraeus crypticus .